Origins of modern art : masterworks of modernism, from Monet and Van Gogh to Kandinsky, Delaunay and Klee - Ormiston, Rosalind; Lloyd, Fran (Fulham, England : Flame Tree Publishing Ltd, 2015)
The roots of Modern Art can be seen in the wild paintings of Turner, but it took the Impressionists and the Pre-Raphaelites to break the classical mode until the final blows were dealt by Kandinsky, Klee and Picasso. Once unleashed, modernism fragmented into many different forms, each of which are explored in this book.
Includes bibliographical references (page 188) and index.
Keywords: Art, Modern -- 19th century; Art, Modern -- 20th century; Art, Modern; Art, Modern -- History